Identification of depression in diabetes: the efficacy of PHQ-9 and HADS-D - Reddy, Prasuna (Royal College of General Practitioners, 2010)
BACKGROUND: Clinical guidelines advise screening for depression in patients with diabetes. The Patient Health Questionnaire (PHQ-9) and the depression subscale of the Hospital Anxiety and Depression Scale (HADS-D) are commonly used in primary care. AIM: To compare the efficacy of HADS-D and PHQ-9 in identifying moderate to severe depression among primary care patients with type 2 diabetes. DESIGN OF STUDY: Self-report postal survey, clinical records assessed by GPs. SETTING: Seven metropolitan and rural general practices in Victoria, Australia. METHOD: Postal questionnaires were sent to all patients with diabetes on the registers of seven practices in Victoria. A total of 561 completed postal questionnaires were returned, giving a response rate 47%. Surveys included demographic information, and history of diabetes and depression. Participants completed both the PHQ-9 and HADS-D. Clinical data from patient records included glycosylated hemoglobin (HbA1c) levels and medications. RESULTS: The proportion of the total sample completing HADS-D was 96.8% compared with 82.4% for PHQ-9. Level of education was unrelated to responses on the HADS-D but was related to completion of the PHQ-9. Using complete data (n = 456) from both measures, 40 responders showed HADS-D scores in the moderate to severe range, compared with 103 cases identified by PHQ-9. Only 35 cases were classified in the moderate to severe category by both the PHQ-9 and HADS-D. Items with the highest proportions of positive responses on the PHQ-9 were related to tiredness and sleeping problems and, on the HADS-D, feeling slowed down. CONCLUSION: It may be that the items contributing to the higher prevalence of moderate to severe depression using the PHQ-9 are due to diabetes-related symptoms or sleep disorders.